Influence of chromium (III) contaminated soil on soil mycobiota - CHOUDHARY, SHIPRA; KUMAR, PERMOD; CHARAYA, M U (The Indian Journal of Agricultural Sciences, 2015)
Investigation was conducted on the experimental fields of CCS University (Meerut) during 2013–2014 to evaluate the influence of Cr (III) contamination on soil mycobiota and to obtain some Cr (III)-resistant strains for the management of Cr (III)-contaminated soils and of the effluents carrying the metal. Blocks (30cm × 30cm) each were treated with different concentrations (500 ppm/1000 ppm/2000 ppm) of chromium (III) nitrate or chromium (III) sulphate solution separately in triplicates. Three blocks served as control. The soil samples collected aseptically from control and treated blocks after 20, 40 and 60 days were analysed for mycobiota using serial dilution plate and soil plate methods. Overall dominance of anamorphic fungi and paucity of mucoraceous fungi was observed amongst the fifty two species of fungi isolated. Aspergillus niger was most tolerant to Cr (III) probably due to binding of Cr (III) by amide, amine and C=S groups on the fungus as revealed by FTIR spectroscopy. Reciprocal relationship between pollutant concentration ‘c’ and time ‘t’ (i.e. constancy of c×t ) did not hold true; such a relationship might be operative for a single species in-vitro systems. Cr (III) salts adversely affected the mycobiota (qualitatively and quantitatively) though not to the extent reported for Cr (VI). The results indicate that though soil fungal diversity is adversely affected by Cr (III) contamination, the surviving species flourish over a period of time leading to the partial recovery of the mycopopulation. Aspergillus niger biomass with Cr (III)-binding functional groups might be utilized for in situ management of Cr (III) in soils and in biosorption-based effluent treatment systems.